1992
DOI: 10.1007/bf00770989
|View full text |Cite
|
Sign up to set email alerts
|

Sintering of Pt/Al2O3 reforming catalysts: EXAFS study of the behavior of metal particles under oxidizing atmosphere

Abstract: The effect of an oxidative atmosphere (300°C) is studied on fresh and sintered unchlori nated naphtha reforming catalysts containing 0.6-1 % Pt. The TPR profiles show that only one species is formed using our experimental conditions, regardless of the mean crystallite size of the metal particles. The structural information supplied by EXAFS compared with cuboctahedral particle modeling, implies that such species is a surface platinum oxide, the structure of which is close to that of Pt02, but largely distorted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
41
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 20 publications
8
41
1
Order By: Relevance
“…On Pt/Al 2 O 3 prepared from chlorinated precursor, Marceau et al [30] indicated the presence of oxy-chlorinated Pt species, which were reduced at 290°C, while Hwang and Yeh [31] reported that dispersed PtO x Cl y species were reduced at a higher reduction temperature (350°C). The high consumption of H 2 (H 2 /Pt = 3.3) in the TPR profile of Pt-Ni/CNTs (I) is in accordance with that already observed on 5% Pt/ZnO [18] or in Pt/Al 2 O 3 [32][33][34][35][36] which was interpreted by the …”
Section: H 2 -Tprsupporting
confidence: 87%
“…On Pt/Al 2 O 3 prepared from chlorinated precursor, Marceau et al [30] indicated the presence of oxy-chlorinated Pt species, which were reduced at 290°C, while Hwang and Yeh [31] reported that dispersed PtO x Cl y species were reduced at a higher reduction temperature (350°C). The high consumption of H 2 (H 2 /Pt = 3.3) in the TPR profile of Pt-Ni/CNTs (I) is in accordance with that already observed on 5% Pt/ZnO [18] or in Pt/Al 2 O 3 [32][33][34][35][36] which was interpreted by the …”
Section: H 2 -Tprsupporting
confidence: 87%
“…Three main peaks were observed in all cases. Since hydrogen hexachloroplatinate was used as the platinum precursor, the first two peaks located at 200 and 240°C (II and III) can be referred to as the reduction of threedimensional bulk phase of oxy-or hydroxychlorinated platinum while the high temperature peak located at 360°C (IV) is referred to the reduction of the twodimensional dispersive oxychlorinated platinum [23][24][25].…”
Section: Hydrogen/co Chemisorptionmentioning
confidence: 99%
“…QEXAFS shows that PtO x is formed after calcination. It is most likely that also PtO x particles have the ability to sinter (39) and ultimately form larger Pt particles.…”
Section: The Final Metal-particle Size: Processes Leading To Narrow Pmentioning
confidence: 99%